Pewna klasa losowych profili prędkości - Chmielniak, T. (Engineering Transactions, 1969)
The paper concerns the determination of statistical chance characteristics of velocity profiles. and values of friction for flow along an infinite plane wall with an assumed constant velocity of fluid sucking off. The velocity of the potential stream is a time chance function of known expectation value and correlation function. Utilizing the method of correlation analysis the expectation values were determined of the processes (2.1) and (2.3) the correlation function (2.2) and (2.4) and the mean squares of velocity and friction (2.5), (2.6) were determined. The given solutions have been selectedfor a several assumed stochastic courses (stationary and nonstationary) of the velocities of the potential stream. The more interesting results have been illustrated with figures.